2022
DOI: 10.3390/jfb13040175
|View full text |Cite
|
Sign up to set email alerts
|

Important Roles and Potential Uses of Natural and Synthetic Antimicrobial Peptides (AMPs) in Oral Diseases: Cavity, Periodontal Disease, and Thrush

Abstract: Numerous epithelial cells and sometimes leukocytes release AMPs as their first line of defense. AMPs encompass cationic histatins, defensins, and cathelicidin to encounter oral pathogens with minimal resistance. However, their concentrations are significantly below the effective levels and AMPs are unstable under physiological conditions due to proteolysis, acid hydrolysis, and salt effects. In parallel to a search for more effective AMPs from natural sources, considerable efforts have focused on synthetic sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 243 publications
(148 reference statements)
0
6
0
Order By: Relevance
“…Dong et al 18 reported that biological antibacterial polypeptide periodontal gel significantly improved the clinical signs of patients with peri‐implant inflammation. Luong et al 19 presented that AMPs effectively treated periodontitis. In our study, the total effective rate of the study group was greatly higher than that of the control group after treatment ( p < 0.05), which was consistent with earlier studies, 18,19 indicating the curative effect of periodontitis was improved after the adjuvant treatment of biological antibacterial polypeptide periodontal gel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dong et al 18 reported that biological antibacterial polypeptide periodontal gel significantly improved the clinical signs of patients with peri‐implant inflammation. Luong et al 19 presented that AMPs effectively treated periodontitis. In our study, the total effective rate of the study group was greatly higher than that of the control group after treatment ( p < 0.05), which was consistent with earlier studies, 18,19 indicating the curative effect of periodontitis was improved after the adjuvant treatment of biological antibacterial polypeptide periodontal gel.…”
Section: Discussionmentioning
confidence: 99%
“…Luong et al 19 presented that AMPs effectively treated periodontitis. In our study, the total effective rate of the study group was greatly higher than that of the control group after treatment ( p < 0.05), which was consistent with earlier studies, 18,19 indicating the curative effect of periodontitis was improved after the adjuvant treatment of biological antibacterial polypeptide periodontal gel. In vitro experiments supported by Xie et al 20 showed that the biological antibacterial polypeptide periodontal gel reached the maximum bactericidal effect and minimum cytotoxic effect within the concentration range of 10–20 mg/L, without affecting the formation of alveolar bone.…”
Section: Discussionmentioning
confidence: 99%
“…They interact with microbial cell membranes, leading to cell lysis. Synthetic AMP analogs have exhibited anti-H. pylori activity [37,38]. AMPs produced by gastric epithelial cells regulate the bacterial population in the stomach, but H. pylori has evolved resistance mechanisms [39][40][41].…”
Section: Alternative Approaches For H Pylori Treatmentmentioning
confidence: 99%
“…Despite their effectiveness, H. pylori has evolved specific resistance mechanisms against host AMPs. The development of new synthetic AMP analogues and further research is actively underway [37,38,[48][49][50].…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…These microorganisms are mostly responsible for the two types of oral disorders, dental caries, and gingival bleeding/periodontitis. Dental caries and periodontitis are not caused by a single causal pathogen, instead by a polymicrobial community that functions synergistically [2,3]. Dental disorders may induce systemic, cardiovascular, and brain diseases if not addressed promptly [4,5].…”
Section: Introductionmentioning
confidence: 99%